Circulating tumor cells as prognostic biomarkers in breast cancer: current status and future prospects. (3rd October 2021) - Chantzara, Evagelia; Xenidis, Nikolaos; Kallergi, Galatea; Georgoulias, Vassilis; Kotsakis, Athanasios
ABSTRACT: Introduction : Despite advances in diagnostic and therapeutic techniques breast cancer is still associated with significant morbidity and mortality. CTCs play a crucial role in the metastatic process, which is the main cause of death in BC patients. Areas covered : This review discusses the prognostic and predictive value of CTCs and their prospective in management of BC patients. Expert opinion : The analysis of CTCs through improved technologies offers a new insight into the metastatic cascade. Assessment of the number and molecular profile of CTCs holds great promises for disease monitoring and therapeutic decisions. However, more research is needed until they can be used in therapeutic decisions in clinical practice.